Mathematical, electrochemical, spectroscopic and microscopic monitoring of the adsorption effect of expired drugs on zinc corrosion in 3.5% NaCl solution - Arafat Toghan; Omar K. Alduaij; Nada Alqarni; Emad M. Masoud; Hanan Alhussain; Ayman M. Mostafa; Ahmed A. Farag; Ahmed Fawzy (Results in Chemistry)
Because of its unique properties, zinc is widely used in many industries, including medical devices, electronics, and automotive components, but it is susceptible to corrosion, especially in salty environments. In this context, the inhibitory efficacy of two environmentally friendly expired drugs, gatifloxacin (Gat) and levofloxacin (Lev), on zinc corrosion in 3.5 % NaCl solution was investigated using several techniques at different temperatures. Kinetic and thermodynamic evaluations confirmed that the adsorption strength of these compounds on the metal surface plays an effective role in their inhibitory capacity, and this certainly depends on their chemical structure. The inhibition efficiencies (% IEs) were calculated to be 87 % and 89 % for Gat and Lev using 500 mg/L of drug and at 298 K, respectively. Potentiodynamic polarization (PDP) studies have classified these drugs as anodic-type inhibitors. Adsorption assessments have shown that it is a physical process following the Langmuir isotherm. Electrochemical impedance spectroscopy (EIS) experiments have demonstrated good adhesion and stability of the protective film on the metal surface resulting from the adsorption of these compounds. Inhibition mechanisms have also been provided. Response surface methodology (RSM) analysis was used to analyze the data and predict the response. The experimental results of all the techniques used and the statistical and computational analysis were in remarkable agreement with each other.